La gestión administrativa en el Colegio "JATARI UNANCHA" y su incidencia en la imagen institucional, peíodo enero a julio del 2014. - Hidalgo Copara, Aída Marlene (2016)
The study entitled: Administrative management in "Jatari Unancha" School and its impact on institutional image, from January to July 2014, had its principal aim to meet the administrative processes in different educational establishments which belong to the school and institutional image structure by members of the educational community. To achieve this purpose theoretical information of the variables used to justify research was collected. The methodology used is the deductive method as it goes from the general to the particular. The research is descriptive since it involves getting to know the situations prevailing customs and attitudes through the exact description of activities, objects, processes and people. Existing population at Jatari Unancha School is extensive, so that the selection of the sample was performed by applying sampling formula. To collect data three questionnaires interview aimed at parents, students and teachers was designed. The results of the research show that the quality of service provided by the school to the educational community is excellent, quick and efficient; it projects a positive institutional image among its members, so the research hypothesis was verified. The research work will bring to the educational community, trust and growth of the school, while managers will allow correcting existing weaknesses.